Pengaruh Pendekatan Eksplorasi Lingkungan Terhadap Pengetahuan Sains Anak Usia Dini di Raudhatul Athfal Ar Rahmah Medan - Maysarah Rabiul Aulia Damanik; Humaidah Br. Hasibuan; Raisah Armayanti Nasution (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research was carried out at Raudhatul Atfal RA Ar Rahmah Medan. The type of this study is a quantitative experiment with a Quasi Experimental Design with a Non-Equivalent Control Group Design. The population of this study is 26 children, so because the population is less than 100, the sample determination uses random sampling techniques. The formulation of this research problem: How is early childhood science knowledge in RA Ar Rahmah, and is there an effect of the application of the environmental exploration approach on early childhood science knowledge at RA Ar Rahmah. This study aims to find out: (1) early childhood science knowledge in RA Ar Rahmah (2) the influence of the application of the environmental exploration approach on early childhood science knowledge at RA Ar Rahmah. From the results of the study, there was an average score of 53.84 for the pre-test experimental class and an average of 70 for the post-test, with the highest score of 80 for the post test and the lowest score for the 60 post-test. The control class with an average pre-test score of 47.30 and an average post test score of 68.84, with the highest score of 80 and the lowest score of 60. The results of the hypothesis test were obtained > ttable, which was 0.20 > 1.71387 with a significant number of α= 0.05. Thus, Ho's hypothesis was rejected and Ha accepted so that it can be stated that there is a significant influence between the application of environmental exploration to early childhood science knowledge at RA Ar Rahmah Medan Estate, Percut Sei Tuan District, Medan City T.A 2023/2024. Keywords: , .